PENGARUH FINANCIAL LITERACY DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN VIRTUAL GOODS GAME ONLINE MOBILE LEGENDS - Saputri, Ika; Sucipto, Rakhmat Hadi (LPPM Universitas Nusa Mandiri, 2023)
Consumer behavior in purchasing virtual items in online games excessively will result in a decrease in personal financial stability. The problem is caused by a lack of knowledge about financial literacy. The quantitative statistical method was used as a data collection method in this study. The population of this study were Mobile Legends online game users in Pacitan City, with 97 respondents selected as samples using the Chocran formula through purposive sampling techniques. Primary data was collected through questionnaires, while secondary data was obtained through literature studies. Multiple linear regression analysis was used to analyze the research data. The results of multiple linear regression testing show the regression coefficient for each variable, with an α (constant) value of -3.191, a financial literacy regression coefficient (X1) of 0.297, and a price regression coefficient (X2) of 0.719. Partially, the results showed that financial literacy and price have a positive and significant influence on purchasing decisions for virtual goods in the Mobile Legends online game in Pacitan City. While the simultaneous test results show f-count 170.508> 3.09 f-table with a significance value of 0.000 <0.05.